2000
DOI: 10.1385/abab:89:2-3:151
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Sensors of Ultraviolet Radiation Based on recA'::lux Fusions

Abstract: Escherichia coli strains containing plasmid-borne fusions of the recA promoter-operator region to the Vibrio fischeri lux genes were previously shown to increase their luminescence in the presence of DNA damage hazards, and thus to be useful for genotoxicant detection. The present study expands previous work by demonstrating and investigating the luminescent response of these strains to ultraviolet radiation. Several genetic variants of the basic recA'::lux design were examined, including a tolC modification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…At studying of SOS-system activity the recombinant bioluminescent strain of Escherichia coli recA'::lux containing plasmid-borne fusions of the recA promoter-operator region to the Photorhabdus luminescens ZM 1 lux genes (GosNIIgenetika, Russia) was used. Increase of their luminescence in the presence of DNA damage factors [Rosen et al, 2000], were shown previously. Investigation of the luminescent response of this strain to UV radiation allows quantitatively estimate in a real time a SOS-system induction.…”
Section: Bacterial Strainsupporting
confidence: 71%
“…At studying of SOS-system activity the recombinant bioluminescent strain of Escherichia coli recA'::lux containing plasmid-borne fusions of the recA promoter-operator region to the Photorhabdus luminescens ZM 1 lux genes (GosNIIgenetika, Russia) was used. Increase of their luminescence in the presence of DNA damage factors [Rosen et al, 2000], were shown previously. Investigation of the luminescent response of this strain to UV radiation allows quantitatively estimate in a real time a SOS-system induction.…”
Section: Bacterial Strainsupporting
confidence: 71%
“…A hallmark of the exposure of E. coli to conditions or agents that lead to DNA damage is the induction of the SOS response (42). Because SOS induction occurs primarily at the transcriptional level, fusions between the recA, uvrA, sulA, dinD, or cda promoters and the Vibrio fischeri luxCDABE (12) and for the detection of bioantimutagens (35), UV irradiation, and genotoxins (5,25,27,28,41). Here, we selected the SOS-inducible promoter of the cell division inhibitor SulA since a -borne sulA::lacZ fusion is available (30) and because sulA is the most tightly repressed and highly inducible SOS gene characterized to date (32).…”
Section: Resultsmentioning
confidence: 99%
“…recA promoter served as a positive control, as it is SOSregulated and induced by numerous DNA-damaging agents, including MitC Rosen et al, 2000;Van Dyk et al, 2001a). Following a short lag phase, induction of the wild-type Pce1a was rapid and reached a response ratio of 80 within 2.5 h. The single mutant retaining the non-consensus LexA binding site (2/+) had a pattern of induction similar to that observed for the wildtype promoter, but with a 17-fold lower response ratio.…”
Section: The Dual Lexa Binding Sites Of the Colicin E1 Promotermentioning
confidence: 99%